The impact of a future solar minimum on climate change projections in the Northern Hemisphere - G Chiodo; R García-Herrera; N Calvo; J M Vaquero; J A Añel; D Barriopedro; K Matthes (Environmental Research Letters, 2016)
Solar variability represents a source of uncertainty in the future forcings used in climate model simulations. Current knowledge indicates that a descent of solar activity into an extended minimum state is a possible scenario. With aid of experiments from a state-of-the-art Earth system model,we investigate the impact of a future solar minimum on Northern Hemisphere climate change projections. This scenario is constructed from recent 11 year solar-cycle minima of the solar spectral irradiance, and is therefore more conservative than the ‘grand’ minima employed in some previous modeling studies. Despite the small reduction in total solar irradiance (0.36 W m ^−2 ), relatively large responses emerge in the winter Northern Hemisphere, with a reduction in regional-scale projected warming by up to 40%. To identify the origin of the enhanced regional signals, we assess the role of the different mechanisms by performing additional experiments forced only by irradiance changes at different wavelengths of the solar spectrum. We find that a reduction in visible irradiance drives changes in the stationary wave pattern of the North Pacific and sea–ice cover. A decrease in UV irradiance leads to smaller surface signals, although its regional effects are not negligible. These results point to a distinct but additive role of UV and visible irradiance in the Earth’s climate, and stress the need to account for solar forcing as a source of uncertainty in regional scale projections.